An Evaluation of the Dough Rheology and Bread Quality of Replacement Wheat Flour with Different Quinoa Particle Sizes - Ionica Coţovanu; Silvia Mironeasa (Agronomy, 2022)
A way to improve the nutritional value of refined wheat flour with enhanced dough rheology is by substituting wheat flour with quinoa flour (QF) at different addition levels and particle sizes (PS). Experimental variation prediction of the flour α-amylase activity, dough rheological properties, and bread characteristics were estimated using mathematical models. A decrease in the falling number index, water absorption, speed of protein weakening, gas retention coefficient in the dough, maximum creep-recovery compliance, and bread volume and firmness was achieved with the increase of PS. When the QF addition level rose, the values of the following parameters decreased: dough stability, starch retrogradation, dough extensibility and deformation energy, viscosity factor, maximum gelatinization temperature, creep-recovery compliance, and bread quality parameters. Dough rheological properties are important for showing the behavior during processing, which impacts the bread quality. For each quinoa flour PS has identified the optimal addition level in wheat flour for improving bread quality. The best composite flours, regarding dough rheology and bread characteristics, contain 9.13% for large, 10.57% for medium, and 10.25% for small PS. These results may help to improve the quality of refined wheat bread or to range diversify the bread making products.